RNA-seq data from mature male gonads of marine mussels Mytilus edulis and M. galloprovincialis - Angel P. Diz; Mónica R. Romero; Andrés Pérez-Figueroa; Willie J. Swanson; David O.F. Skibinski (Data in Brief, 2018)
The mussels Mytilus edulis and Mytilus galloprovincialis are marine organisms with external fertilization able to hybridize where their distributions overlap allowing the study of reproductive isolation mechanisms in nature. We provide raw data of a transcriptomic analysis of mature male gonads from these two Mytilus spp. using NGS (Illumina) technology and a preliminary list of transcript that were functionally annotated showing species-specific differential expression. A shortlist including some of these genes and their corresponding proteins have been thoroughly analysed and discussed in Romero et al. (2018, Submitted for publication). Keywords: Invertebrates, Mollusks, Mature male gonads, Transcriptomics, Illumina paired-end, De novo sequencing